Novel Insights on MRGPRX2-Mediated Hypersensitivity to Neuromuscular Blocking Agents And Fluoroquinolones - Elst, Jessy; Maurer, Marcus; Sabato, Vito; Faber, Margaretha A.; Bridts, Chris H.; Mertens, Christel; Van Houdt, Michel; Van Gasse, Athina L.; van der Poorten, Marie-Line M.; De Puysseleyr, Leander P.; Hagendorens, Margo M.; Van Tendeloo, Viggo F.; et al. (Frontiers in Immunology, 2021)
Neuromuscular blocking agents like atracurium and rocuronium as well as fluoroquinolones cause mast cell-mediated anaphylaxis by activating Mas-related G protein-coupled receptor X2 (MRGPRX2), but many questions remain unanswered. Here, we address three of them, namely whether primary human mast cells show similar activation by these drugs as murine mast cells and mast cell lines, how sugammadex protects from atracurium-induced MRGPRX2-mediated mast cell activation, and why some but not all patients treated with rocuronium develop anaphylaxis. We used peripheral blood-derived cultured mast cells from healthy donors and patients, assessed mast cell activation and degranulation by quantifying intracellular calcium and CD63 expression, respectively, and made use of MRGPRX2-silencing, via electroporation with Dicer-substrate small interfering RNAs, and single cell flow cytometric analyses. Atracurium, ciprofloxacin, and levofloxacin activated and degranulated primary human mast cells, but only MRGPRX2-positive and not MRGPRX2-negative or -silenced mast cells. Sugammadex attenuated the atracurium-induced and MRGPRX2-mediated activation and degranulation of human mast cells by reducing free atracurium levels. The mast cells of patients with IgE-independent anaphylaxis to rocuronium were similar, in their MRGPRX2 expression and function, to those of patients with IgE-mediated anaphylaxis. These findings further our understanding of the role and relevance of MRGPRX2-driven mast cell activation in anaphylactic reactions to NMBAs and FQs and may help to improve their prediction, prevention, and treatment.